An analysis of variable costs in small great plain meat processors with a focus on food safety costs - Callis, William (Kansas State University, 2014)
The United States has been inspecting commercial meat processing for over 100 years. Currently there is a push to increase the number of bacteria that meat processors are responsible to test for, which would lead to an increase in the costs of production. The goal of this thesis was to investigate antimicrobial practices used in small beef processing facilities across the Great Plains and the costs associated with those practices. A survey instrument was constructed and administered resulting in a total of 39 usable surveys for analysis. Preliminary analysis of the data was followed by an ordinary least squares regression to determine cost increasing or decreasing practices and attributes of the small processors. It was determined that on average small meat processors face a per ton variable cost of $914.71 or $0.46 per pound. Regression analysis indicated that plants can benefit from economies of scale. It was also determined there are no cost savings from being a state inspected as opposed to a federally inspected plant. Certain practices such as dry aging beef to increase quality and decrease bacterial load were found to increase the variable cost per pound. Microbial testing accounted for only 0.5% of the total variable cost of production.
Keywords: Food Safety; Meat Safety; HACCP; Food Safety Cost; Economics, Agricultural (0503)